Transcriptional Responses of Flavin-Containing Monooxygenase Genes in Scallops Exposed to PST-Producing Dinoflagellates Implying Their Involvements in Detoxification - Kong, Lingling; Liu, Pingping; Li, Moli; Wang, Huizhen; Shi, Jiaoxia; Hu, Jingjie; Li, Yueru; Hu, Xiaoli (Frontiers in Marine Science, 2021)
Flavin-containing monooxygenase (FMO) is one of the most prominent xenobiotic metabolic enzymes. It can catalyze the conversion of heteroatom-containing chemicals to polar, readily excretable metabolites and is considered an efficient detoxification system for xenobiotics. Bivalves can accumulate paralytic shellfish toxins (PSTs) produced by dinoflagellates, especially during outbreaks of harmful algal blooms. Exploring FMO genes in bivalves may contribute to a better understanding of the adaptation of these species and the mechanisms of PSTs bioavailability. Therefore, through genome screening, we examined the expansion of FMO genes in two scallops (Patinopecten yessoensis and Chlamys farreri) and found a new subfamily (FMO_like). Our expression analyses revealed that, in both scallops, members of the FMO_N-oxide and FMO_like subfamilies were mainly expressed from the D-stage larvae to juveniles, whereas the FMO_GS-OX subfamily genes were mainly expressed at and prior to the trochophore stage. In adult organs, higher expressions of FMOs were observed in the kidney and hepatopancreas than in other organs. After exposure to PST-producing algae, expression changes in FMOs occurred in hepatopancreas and kidney of both scallops, with more members being up-regulated in hepatopancreas than in kidney for Alexandrium catenella exposure, while more up-regulated FMOs were found in kidney than in hepatopancreas of C. farreri exposed to A. minutum. Our findings suggest the adaptive functional diversity of scallop FMO genes in coping with the toxicity of PST-producing algae.